Electrical properties of sodium potassium niobate/mullite ceramic composites - Narumon Lertcumfu (2018)
© 2017 Taylor & Francis Group, LLC. In the present study, the composites between KNN and mullite were fabricated via a solid-state reaction technique. KNN was calcined at 900°C and mullite which synthesized from kaolinite (Ranong, Thailand) was calcined at 1300°C. Effects of KNN content on the composites properties such as densification and electrical properties including dielectric, ferroelectric and piezoelectric properties have been investigated. It was found that the densification behavior of the composites was improved by KNN added. The addition of KNN also resulted in improvements of electrical properties such as remanent polarization, dielectric constant, and piezoelectric coefficient of the materials.